Understanding the Conductive Carbon Additive on Electrode/Electrolyte Interface Formation in Lithium-Ion Batteries via in situ Scanning Electrochemical Microscopy - Liu, Shuai; Zeng, Xiaojie; Liu, Dongqing; Wang, Shuwei; Zhang, Lihan; Zhao, Rui; Kang, Feiyu; Li, Baohua (Frontiers in Chemistry, 2020)
The role of conductive carbon additive on the electrode/electrolyte interface formation mechanism was examined in the low-potential (3.0 0 V) and high-potential (3.0 - 4.7 V) regions. Here the most commonly used conductive carbon Super P was used to prepared electrode with polyvinylidene fluoride binder without any active material. The dynamic process of interface formation was observed with in situ Scanning Electrochemical Microscopy. The electronically insulating electrode/electrolyte passivation layer with areal heterogeneity was formed after cycles in both potential regions. The low-potential interface layer is mainly composed of inorganic compounds covering the conductive carbon surface; While the electrode after high-potential sweep tend to loss its original carbon structure and have organic species formed on its surface.